Czech Koruna and Polish Zloty : Spot and Currency Option Volatility Patterns - Mendez Morales, Armando (IMF Working Papers; Working Paper ;, 2001)
Exchange rate flexibility has facilitated an impressively fast insertion of the Czech koruna and the Polish zloty into the global currency market. However, exchange rate volatility patterns differ: Lower volatility is observed for the koruna against the euro relative to the U.S. dollar, while the opposite is true for the zloty, apparently related to earlier financial integration of the Czech Republic with Europe and early dollarization in Poland as a result of initial higher inflation rates. By contrast, the currency options market shows enhanced information content of both currencies against the euro reflected in the behavior of their implied volatility.